ENHANCING THE PERFORMANCE OF SMEs POST COVID-19: THE ROLE OF STRATEGIC LEADERSHIP CAPABILITIES - Peter, Fred Ojochide; Adeniyi, Mojisola Mubo; Sajuyigbe, Ademola; Peter, Adeshola Oluwaseyi; Adeoti, Sarah Bunmi (Journal of Business And Entrepreneurship, 2023)
Small and medium enterprises had difficulty coping with the Covid-19 pandemic as very few SMEs have made it through it, particularly in Nigeria. Strategic leadership has been acknowledged as a crucial asset and one of the driving forces of success among SMEs. This study examined the impact of strategic leadership on the performance of SMEs in Lagos, Nigeria, adopting a mixed-method approach. A total of 400 complete responses from SME managers were analyzed. While simple regression was applied for the analysis of the returned copies of the questionnaire, the qualitative interview results were obtained through thematic analysis. The results indicate that innovation capabilities significantly impact organizational performance. Hence, the study recommends that focusing on innovative capability of strategic leadership such as new product development, innovation activities, marketing intelligence, value creation and new ideas with radical changes are germane for enhancing performance.